Viabilidade econômica de um projeto de produção de energia elétrica via biomassa florestal : estudo de caso a partir da Usina Santa Terezinha de Paranacity - Seratto, Celso Daniel (2010)
In light of the Schumpeterian theory of origin, this work evaluates the feasibility of an innovation project, incremental process, oriented for the firm which was developed in a case study for the Unit Thermal Power Plant of Santa Terezinha in Paranacity, Parana State, Brazil. The project uses the idle capacity of the thermogenerator system of extraction and condensation, compensating the period between harvests of sugar cane aiming to increase the production of electricity and carbon credits and supplying the deficit of conventional fuel (bagasse) with forest biomass originated by eucalyptus chips, which could be cultivated in 5059.8ha of rented land. Indeed this work states the use of agricultural equipment and transport available, in addition to acquire insumes and implements designed to forest cultivation with funding through BNDES, and the machinery and equipment designed for mechanized harvesting processing of biomass must be purchased through leasing credit system. The economic and financial viability analysis was made through a projection of 18 years, using the technique of discounted cash flow and the criteria of TIR, NPV and payback at the rate of discount equivalent to the TMA of 13.75% per year. The influence of costs with transport and others referred to logistics was tested by using the effect of variation in the mean radius of the forest dedicated areas. Then, the innovation project results indicated that there is an economic viability if the areas of forest cultivation are found distant until 117.77 km of the Plant, which would reduce the payback of the current design development of 13.10 to 11.90 years. However, if the mean radius is 30 km, the project may provide a payback of 10.49 years and NPV of R$10,489,586.13. Thus, if considered technical, environmental and political-institutional aspects, it is possible to conclude that the project is feasible and could lead to ulterior innovations into the local economy, since the portion produced in 20% of the remaining areas destined to payment for rented areas, increases the supplying of wood of Eucalyptus sp. into the project area. However, it was identified that a competitive price for the Plant to acquire biomass allows the purchase of third parties until a distance of 22.93 km, which, however, allows build a strong connection between agroenergy and forest production chains which support the creation of public policies, encouraging the inclusion of farmers in this production process aiming to regional development.